2014
DOI: 10.7762/cnr.2014.3.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Intervention for a Patient with Diabetic Nephropathy

Abstract: In recent years, several studies have reported that the prevalence of diabetes mellitus is increasing every year, and also the acute and chronic complications accompanying this disease are increasing. Diabetic nephropathy is one of chronic complications of diabetes mellitus, and food intake which is burden to kidney function should be limited. At the same time, diet restriction could deteriorate quality of life of patient with diabetic nephropathy. According to the results of previous studies, the aggressive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…DN occurs in 20% to 40% of patients with diabetes and is the most likely cause of end-stage renal disease reported worldwide [ 6 ]. Although numerous factors contributing to the development of diabetic complications including DN have been proposed, AGEs are thought to be of major importance [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…DN occurs in 20% to 40% of patients with diabetes and is the most likely cause of end-stage renal disease reported worldwide [ 6 ]. Although numerous factors contributing to the development of diabetic complications including DN have been proposed, AGEs are thought to be of major importance [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sarcopenia is the progressive generalized loss of skeletal muscle mass, strength, and function. Although sarcopenia is essentially a disorder of advanced age, it can also occur at younger ages secondary to chronic nutritional problems, chronic diseases, malignancies, low level of physical activity, some drugs side effects ( 1 , 2 ). Chronic kidney disease (CKD) can lead to sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“…The induction of insulin resistance by high fructose diet was considered to enhance impaired glucose tolerance in the high fructose-fed SDT rats. In humans, high blood glucose level is one of the risk factors for DN of diabetes patients (Delahanty and Halford, 1993;Kim, 2014). Therefore, elevation of plasma glucose levels in the SDT rats fed a high fructose diet was considered to contribute to progression of the kidney injury.…”
Section: D a B E Fmentioning
confidence: 99%
“…Some recent trials report that strict blood glucose management using a carbohydrate-limited diet ameliorates hyperglycemia and such carbohydrate management is effective for delaying of the progression to DN (Delahanty and Halford, 1993;Kim, 2014). While the intake of glucose is one of the most important factors influencing the development of diabetes and DN, some studies revealed that other nutrients also contribute to the progression of diabetes and DN.…”
Section: Introductionmentioning
confidence: 99%